Effectiveness of photobiomodulation therapy in accelerating orthodontic tooth movement: a meta-analysis of randomized clinical trials. - Naira Figueiredo Deana; Nilton Alves; Paulo Sandoval (Universidad de Concepción., 2019)
To assess the effectiveness of photobiomodulation therapy (PBMT) in accelerating orthodontic tooth movement (OTM). Material and Methods: A systematic review was carried out in MEDLINE, Cochrane Library, EMBASE and LILACS of articles in English, Portuguese and Spanish. Additional studies were identified by searching bibliographies. The search terms included: randomized controlled trial (RCT), low-level laser therapy, phototherapy, orthodontic wires, orthodontic anchorage procedures, activator appliances. Study Selection: Only RCTs which analyzed the effect of PBMT in accelerating OTM were included. Independent extraction of articles by two authors using predefined data fields, including study quality indicators was performed. The risk of bias of the eligible trials was assessed using the Cochrane Collaboration's risk of bias tool. Mean difference was calculated and pooled by meta-analysis using random effect models. The quality of the evidence was assessed using GRADE Pro. Results: Fourteen RCTs analysing tooth movement in the canine retraction (CR) phase and two studies in the tooth alignment phase were included in the qualitative analysis; 68.75% of the RCTs reported that PBMT was effective in accelerating OTM. Nine studies presented 'unclear risk of bias' and seven presented 'high risk of bias'. Mean difference was calculated and pooled by meta-analysis using random effect models. Twelve studies presented sufficient information for inclusion in the meta-analysis. Photobiomodulation doses between 50 and 75 J/cm2 were effective in accelerating OTM in months 1, 2 and 4 of CR, and in increasing the accumulated CR rate. The quality of the evidence was downgraded due to the risks of bias, imprecision or considerable heterogeneity of the studies. Conclusions: PBMT treatment with low or very high application of total/per tooth ED is not effective in accelerating OTM. Application of energy density (ED) between 50 and 75 J/cm2 per tooth was effective in accelerating OTM after 1 and 2 months of CR, as well as in increasing the accumulated CR rate.